Belatacept: a new era of immunosuppression?. (August 2012) - El-Charabaty, Elie; Geara, Abdallah Sassine; Ting, Christopher; El-Sayegh, Suzanne; Azzi, Jamil
Full T-cell activation in alloimmunity requires the engagement of several costimulatory molecules. CTLA-4-Ig and its commercially available fusion proteins, belatacept and abatacept, are used to block CD80/86 and promote T-cell tolerance. Belatacept, a higher binding affinity molecule, is currently approved for clinical use in renal transplantation. The results of two Phase III clinical trials showed a similar patient/graft survival, with better renal function at a 3-year follow-up compared with conventional immunosuppression. There was a higher risk of early rejection and post-transplant lymphoproliferative disorder, especially with EBV-negative patients receiving kidneys from EBV-positive donors. Belatacept-treated groups had a better cardiovascular and metabolic profile. The authors review both preclinical and human studies of CTLA-4-Igs.